ADAMTS13 exerts a thrombolytic effect in microcirculation - Crescente, Marilena; Thomas, Grace M.; Demers, Melanie; Voorhees, Jaymie R.; Wong, Siu Ling; Ho-Tin-Noé, Benoit; Wagner, Denisa D. (Thrombosis and Haemostasis, 2012)
Recombinant tissue plasminogen activator (r-tPA) is the drug of choice for thrombolysis, but it is associated with a significant risk of bleeding and is not always successful. By cleaving von Willebrand factor (VWF), the metalloprotease ADAMTS13 (a disintegrin-like and metalloprotease with thrombospondin type I repeats-13) down-regulates thrombus formation in injured vessels. We investigated whether recombinant ADAMTS13 (r-ADAMTS13) induces thrombolysis in vivo in mice. Thrombosis was produced by ferric chloride-induced (FeCl3) injury in the venules of a dorsal skinfold chamber. Phosphate-buffered saline (PBS, vehicle), r-tPA or r-ADAMTS13, supplemented with hirudin (to stop ongoing thrombin generation), was directly applied onto the occluded vessel, and thrombus dissolution was evaluated by intravital microscopy. The incidence of blood flow restoration significantly increased 30 minutes (min) after r-ADAMTS13 vs. PBS treatment (60% vs. 0%, p<0.05) and 60 min after r-tPA treatment (75% vs. 17%, p<0.05). Both r-tPA and r-ADAMTS13 significantly reduced thrombus size 60 min after their superfusion (53.2% and 62.3% of the initial thrombus size, p<0.05 and p<0.01, respectively). Bleeding occurred in all r-tPA-treated chambers, while it was absent in mice treated with r-ADAMTS13 or PBS. We observed that, similar to r-tPA, r-ADAMTS13 can dissolve occlusive thrombi induced by FeCl3 injury in venules. In contrast to r-tPA, the in vivo thrombolytic effect of ADAMTS13 was not associated with any signs of haemorrhage. ADAMTS13 could represent a new therapeutic option for thrombolysis.
Keywords: ADAMS/ADAMTS 13; thrombolysis / thrombolytic agents; plasminogen activators; intravital microscopy